The Whiteley Index–6: An Examination of Measurement Invariance Among Self-Identifying Black, Latino, and White Respondents in Primary Care. (March 2018) - Fergus, Thomas A.; Kelley, Lance P.; Griggs, Jackson O.
Brief measures that are comparable across disparate groups are particularly likely to be useful in primary care settings. Prior research has supported a six-item short form of the Whiteley Index (WI), a commonly used measure of health anxiety, among English-speaking respondents. This study examined the measurement invariance of the WI-6 among Black ( n = 183), Latino ( n = 173), and White ( n = 177) respondents seeking treatment at a U.S. community health center. Results supported a bifactor model of the WI-6 among the composite sample ( N = 533), suggesting the presence of a general factor and two domain-specific factors. Results supported the incremental validity of one of the domain-specific factors in accounting for unique variance in somatic symptom severity scores beyond the general factor. Multiple-groups confirmatory factor analysis supported the configural, metric, ands scalar invariance of the bifactor WI-6 model across the three groups of respondents. Results provide support for the measurement invariance of the WI-6 among Black, Latino, and White respondents. The potential use of the WI-6 in primary care, and broader, settings is discussed.